2006
DOI: 10.5551/jat.13.82
|View full text |Cite
|
Sign up to set email alerts
|

Significant Expression of Endoglin (CD105), TGFβ-1 and TGFβ R-2 in the Atherosclerotic Aorta: An Immunohistological Study

Abstract: To date, the glycoprotein endoglin and its receptor complex, formed between TGF and TGF R-2, have been studied in tumor angiogenesis. The purpose of this study is to investigate the expression profile of endoglin and its receptor complex in human atherosclerotic lesions, and compare it to that in non-atherosclerotic tissues. Twenty-six atherosclerotic lesions and twenty-six non-atherosclerotic aortic tissues were collected from thirty-six autopsy cases. Indirect immunohistochemical staining was performed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 25 publications
4
35
0
4
Order By: Relevance
“…In general, it is complicated to precisely explain endoglin participation in the regulation of the proposed pathways and atherosclerosis in vivo because endoglin is exclusively expressed in endothelial cells in mice 4,45) , while other members of the cascade, including ALK, Smad proteins and VEGF, are also expressed in the whole vessel wall. Other authors also showed increased endoglin expression in smooth muscle cells, and in macrophages in human and porcine atherosclerotic lesions 8,18) . Unfortunately, we cannot determine precisely how efficiently endoglin regulates the activity of ALKs and Smads since they were only partially expressed on the endothelium together with endoglin in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In general, it is complicated to precisely explain endoglin participation in the regulation of the proposed pathways and atherosclerosis in vivo because endoglin is exclusively expressed in endothelial cells in mice 4,45) , while other members of the cascade, including ALK, Smad proteins and VEGF, are also expressed in the whole vessel wall. Other authors also showed increased endoglin expression in smooth muscle cells, and in macrophages in human and porcine atherosclerotic lesions 8,18) . Unfortunately, we cannot determine precisely how efficiently endoglin regulates the activity of ALKs and Smads since they were only partially expressed on the endothelium together with endoglin in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Endoglin expression has been demonstrated in human 8,16) , porcine 32) and mouse atherosclerotic vessels 4) . Moreover, several in vitro studies have demonstrated the crucial role of endoglin in 33) and activation of the ALK-5/Smad-2 pathway 20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that endoglin is expressed by the aortic vessel endothelium in normo-and hypercholesterolemic mice 6,7) . Moreover, endoglin expression was also detected in human and porcine atherosclerotic lesions 3,4,8) .…”
Section: Introductionmentioning
confidence: 93%
“…In endothelial cells ALK 5/RI inhibits migration and proliferation, unlike ALK1, which induces these two pathways: thus TGFb1 regulates vascular homeostasis by producing a balance between ALK 5/RI and ALK1 signaling [9,53]. Other accessory TGFb1 receptors have been identified, the betaglycan and endoglin type III receptors, which are transmembrane molecules with different roles: betaglycan facilitates the binding of TGFb1 to TbRII, while endoglin (also named CD105) is a glycoprotein which binds ligand only when it is already associated to TbRII and acts as regulator of TGFb1/ALK5 signaling on endothelial homeostasis [32,37,83].…”
Section: How Tgfb1 Signal Influences Colon Mucosa Functionmentioning
confidence: 99%